Cardiac cytochrome c and cardiolipin depletion during anthracycline-induced chronic depression of mitochondrial function - Pereira, Gonçalo C. (2016)
It is still unclear why anthracycline treatment results in a cardiac-specific myopathy. We investigated whether selective doxorubicin (DOX) cardiotoxicity involving mitochondrial degeneration is explained by different respiratory complexes reserves between tissues by comparing and contrasting treatment effects in heart vs liver and kidney. Alternatively, we have also explored if the degeneration is due to alterations of mitochondrial thresholds to incompatible states.